The effect of number of coils on electromagnetic for energy harvester - Noor Aifadilah, Junoh (2012)
The objective of this study is to investigate the performance of the vibration- electromagnetic energy harvester for different number of coils. The relationship between the excitation frequencies and the amount of voltage produced has been analyzed. An electromagnetic energy harvester device was fabricated and tested with three set of coils including 350 turns, 700 turns and 1050 turns. An experiment setup consists of shaker, amplifier, DAQ, PicoScope, and the device. Magnetic material used for the study consists of NdFeB cylinder magnets, copper wire for coils, and aluminum cantilever beam. From the analysis, 350 turns of coils gives 120.156 mV, 219.021 mV for 700 turns and 275.058 mV for 1050 turns. The value of generated voltage is increasing due to the increase number of turn of the coils. The voltage is varying with the increasing of frequency until it pass resonant frequency and then decreasing after it reaches resonant frequency. The potential of this study is widely explore by using the variety of parameters in the experiment such as magnet size, coils diameter and effect of arrangement of magnet to investigate which parameters that have optimum generated output voltage in tend to increase the output voltage.